Reconstructing the Epistemology of the Islamic Religious Education Curriculum Based on the Philosophy of Science to Strengthen Students’ Critical Thinking Skills - Ilham Rozali; Siti Fatimah (Journal of Practice Learning and Educational Development, 2026)
Islamic Religious Education plays a strategic role in shaping students who are faithful, ethical, and intellectually grounded. However, in practice, the curriculum of Islamic Religious Education is still predominantly constructed upon a normative dogmatic paradigm that positions religious knowledge as fixed and final, thereby limiting the development of students’ critical thinking skills. This article aims to examine the reconstruction of the epistemology of the Islamic Religious Education curriculum based on the philosophy of science and its implications for strengthening students’ critical thinking abilities. This study employs a qualitative approach using library research through conceptual and philosophical analysis of literature on the philosophy of science, Islamic epistemology, and the Islamic Religious Education curriculum. The findings indicate that the existing curriculum demonstrates epistemological weaknesses, particularly in integrating revelation, reason, and empirical experience as complementary sources of knowledge. An epistemological reconstruction grounded in the philosophy of science encompassing ontological, epistemological, and axiological dimensions enables Islamic Religious Education to be developed in a more reflective, rational, and contextual manner. This reconstruction contributes to the enhancement of students’ critical thinking through dialogical, analytical, and morally responsible learning processes. The study affirms that the philosophy of science serves as a crucial foundation for the development of an Islamic Religious Education curriculum that transcends mere normative value transmission and functions as a medium for cultivating students’ critical reasoning in contemporary educational contexts.